2022
DOI: 10.3390/biology11020303
|View full text |Cite
|
Sign up to set email alerts
|

Miconazole Mitigates Acetic Acid-Induced Experimental Colitis in Rats: Insight into Inflammation, Oxidative Stress and Keap1/Nrf-2 Signaling Crosstalk

Abstract: Ulcerative colitis (UC) is the most common type of inflammatory bowel disease, characterized by oxidative stress and elevated pro-inflammatory cytokines. Miconazole is an azole antifungal that stimulates the expression of antioxidant enzymes via Nrf2 activation, which consequently inhibits ROS formation and NF-κB activation. Hence, the present study aimed to investigate the protective effect of miconazole, sulfasalazine (as a reference drug) and their combination on acetic acid (AA)-induced UC in a rat model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 58 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…Thus, we evaluated the effect of CRBST on Nrf2 expression in order to investigate its antioxidant and anti-inflammatory properties, and we discovered that AA administration in the UC group significantly reduced Nrf2 expression. Our findings are consistent with prior research that found that AA exposure reduced Nrf2 expression ( Yalniz et al, 2012 ; Alsharif et al, 2022 ). When compared to the UC group, there was a significant increase in Nrf2 after CRBST treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we evaluated the effect of CRBST on Nrf2 expression in order to investigate its antioxidant and anti-inflammatory properties, and we discovered that AA administration in the UC group significantly reduced Nrf2 expression. Our findings are consistent with prior research that found that AA exposure reduced Nrf2 expression ( Yalniz et al, 2012 ; Alsharif et al, 2022 ). When compared to the UC group, there was a significant increase in Nrf2 after CRBST treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress acts as a major partner to the immune system in the pathogenesis of UC and occurs due to the imbalance between the oxidant and antioxidant systems in the colon. This imbalance leads to increased lipid peroxidation ( Alsharif et al, 2022 ) and decreased levels of antioxidant enzymes such as superoxide dismutase (SOD) in colon tissues. Decrease in SOD activity results in compromised detoxifying activity and ultimately free radicals create an oxidative and nitrosative storm ( Elmaksoud et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting oxidative stress and the in ammatory response is a defense mechanism that is mediated by Nfr2 and its downstream antioxidant genes [36]. Speci c genes for antioxidant defense, including SOD, CAT, HO-1, and GSH, are regulated by Nrf2-ARE pathway activation [37]. When Nrf2 is stimulated and translocates to the nucleus, it activates the transcription of anti-oxidant genes through phosphorylation of AKT by activated phosphatidylinositol kinase (PI3K) [38].…”
Section: Discussionmentioning
confidence: 99%